Geochemical of Soil at Gedongsongo Geothermal Prospect Area - T. Listyani R.A.; Ev. Budiadi (Retii, 2017)
Gedongsongo geothermal prospect area is located in Ungaran, Semarang Regency, Central Java. Various geothermal manifestations appeared in the area, such as warm ground, hot spring, rock alteration and fumaroles. Geothermal phenomena is interesting to study, especially on the geochemistry of soil, to see the relationship with geothermal activity. Objective of this study is to determine geological structure and their relationship with geothermal systems by analysis the appearance of some chemical elements in soil. Method of the study were geological and geochemical field study, accompanied by soil sampling. Value of  CO2 of soil were taken directly in field, while H2O and Hg  (mercury) content were determined in the laboratory. Soil geochemistry testing of research area performed by looking at the levels of CO2, H2O and Hg. These three compound anomalies occur in several places, indicating closures around Gedongsongo area. This indication is interpreted closely related with rim structure formed by faults encircling Gedongsongo area. Key words: : geochemistry, soil, mercury, Gedongsongo